Micronutrient intake and fundal height determine birth weight - Faradina Aghadiati; Diffah Hanim; Yulia Lanti Retno Dewi (Intelektual Pustaka Media Utama, 2019)
The birth weight (BW) are utilized as indicators of the healthy and term newborns. Factor that affects the weight of a newborn are micronutrient intake and fundal height. Folic acid and iron (Fe) were associated with newborn birth weight. Fundal height in centimeters (cm) is the same as the gestational age of the week, the fundal height that is not in accordance with the gestational age is leading to stunted fetal growth. The purpose of this study was to analyze the relationship between intake of folic acid, iron (Fe) and fundal height with newborn birth weight. This research method was an analytic observational using a cross-sectional approach. The sample in this study were 114 pregnant women living in Yogyakarta. Statistical test results proved a significant relationship between the intake of folic acid and iron (Fe) with the newborn birth weight (p < 0.05). There was a significant relationship between the fundal height with the newborn birth weight (p < 0.05). The concludes of this study, pregnant women with adequate folic acid intake, adequate iron intake and normal fundal height tended to give birth newborns with normal birth weight.